Landscape controls on water availability limit revegetation after artisanal gold mining in the Peruvian Amazon - Abra Atwood; Shreya Ramesh; Jennifer Angel Amaya; Hinsby Cadillo-Quiroz; Daxs Coayla; Chan-Mao Chen; A. Joshua West (Communications Earth & Environment)
Abstract Deforestation from artisanal, small-scale gold mining is transforming large regions of the tropics, from lush rainforest to barren collections of tailings and ponds. Natural forest regeneration is slow due to dramatic soil changes, and existing reforestation strategies are failing. Here we combine remote sensing, electrical resistivity imaging, and measurements of soil properties to characterize post-mining areas in the Madre de Dios region, Peru. We find that the post-mining landscape has dramatically changed water infiltration dynamics, driving decreases in subsurface water availability and presenting a major barrier to revegetation. Mining tailings are extremely hydraulically conductive, allowing for 14.76 m day−1 infiltration relative to 0.074 m day−1 in primary forest soils, leading to lower average soil moisture and extreme temperatures (60 °C). Electrical resistivity imaging reveals a highly resistive, 1.5–2 m deep layer of dry sand across the mining landscape. Areas close to the water table (e.g., pond edges) show higher soil moisture, lower temperatures, and greater natural regeneration compared to topographically elevated tailings. Our results suggest that access to water should be prioritized when targeting reforestation sites, potentially requiring large-scale geomorphological reconfiguration. As gold mining is expected to expand, responsible practices and remediation strategies must account for the critical yet often overlooked role of water.